1
x + y = 1
(x+1)^ + (y+1)^ = 25
2
3x - 2y =1
(x-2)^ + (2x+3)^ = 26
3
x-5y=8
x^ + 9y^ +3x = 30 + xy
i dont know how to solve but my teacher told me to substitute linear into non-linear.and then put in quadratic . please solve and give me discription how to solve God bless you
^ denotes square
x + y = 1
(x+1)^ + (y+1)^ = 25
2
3x - 2y =1
(x-2)^ + (2x+3)^ = 26
3
x-5y=8
x^ + 9y^ +3x = 30 + xy
i dont know how to solve but my teacher told me to substitute linear into non-linear.and then put in quadratic . please solve and give me discription how to solve God bless you
^ denotes square